Tyrosine kinase activity may be necessary but is not sufficient for c-erbB1-mediated tissue-specific tumorigenicity. - Connolly, D C (1994)
Expression of mutant avian c-erbB1 genes results in tissue-specific transformation in chickens. Site-directed mutagenesis was used to generate kinase-defective mutants of several tissue-specific v-erbB transforming mutants by replacement of the ATP-binding lysine residue in the kinase domain with an arginine residue. These kinase-defective v-erbB mutants were analyzed for their in vitro and in vivo transforming potentials. Specifically, kinase-defective mutants of erythroleukemogenic, hemangioma-inducing, and sarcomagenic v-erbB genes were assessed for their oncogenic potential. In vitro transformation potential was assessed by soft-agar colony formation in primary cultures of chick embryo fibroblasts (CEF). In vivo transformation potential was determined by infection of 1-day-old line 0 chicks with concentrated recombinant retrovirus and then monitoring of birds for tumor formation. These transformation assays demonstrate that kinase activity is absolutely essential for transformation by tissue-specific transforming mutants of the avian c-erbB1 gene. Since all of the tissue-specific v-erbB mutants characterized to date exhibit tyrosine kinase activity in vitro but do not transform all tissues in which they are expressed, we conclude that v-erbB-associated tyrosine kinase activity may be necessary but is not sufficient to induce tumor formation.